Introduction: Urban revolutions in the age of global urbanism. (August 2015) - Sheppard, Eric; Gidwani, Vinay; Goldman, Michael; Leitner, Helga; Roy, Ananya; Maringanti, Anant
This special issue, papers presented at an Urban Studies Foundation-funded conference in Jakarta (March 2011), examines the current 'urban century' in terms of three revolutions. Revolutions from above index the logics and norms of mainstream global urbanism, particularly the form they have taken as policymakers work with municipal officials worldwide to organise urban development around neoliberal norms. Revolutions from below refer to the multifaceted contestations of global urbanism that take place in and around cities, ranging from urban street demonstrations and occupations (such as those riveting the world in early 2011 when these papers were written) to the quotidian actions of those pursuing politics and livelihoods that subvert the norms of mainstream global urbanism. It also highlights conceptual revolutions, referencing the ongoing challenge of reconceptualising urban theory from the South – not simply as a hemispheric location or geopolitical category but an epistemological stance, staged from many different locations but always fraught with the differentials of power and the weight of historical geographies. Drawing on the insights of scholars writing from, and not just about, such locations, a further iteration in this 'southern' turn of urban theorising is proposed. This spatio-temporal conjunctural approach emphasises how the specificity of cities – their existence as entities that are at once singular and universal – emerges from spatio-temporal dynamics, connectivities and horizontal and vertical relations. Practically, such scholarship entails taking the field seriously through collaborative work that is multi-sited, engages people along the spectrum of academics and activists, and is presented before and scrutinised by multiple publics.